Hubungan Tingkat Pendidikan dan Pekerjaan Terhadap Pernikahan Usia Dini Pada Remaja Putri Di Desa Mekar Jaya Kabupaten Tangerang Tahun 2020 - Iis Sumiyati; Andriana Inya Mete; Ahmad Romadloni (Jurnal Obstretika Scientia, 2021)
Marriage is an important event in life. With marriage, a person will get a balance of life both biologically, psychologically and socially. The purpose of this study was to determine the relationship between education and work with early marriage in young women in Mekar Jaya Village, Tangerang Regency.This research is an analytical survey with a cross-sectional approach. Data were collected using quota sampling, amounting to 100 young women, the data were obtained from the Kelurahan in Mekar Jaya Village, Tangerang Regency. This study uses secondary data using a checklist sheet.There was a higher tendency for young women with lower education to marry early. Through the chi-square test, it is known that there is a relationship between education and early marriage (P-value 0,000) and there is no relationship between work and early marriage in young girls (p-value 0.675).It is hoped that related agencies will continue to take promotional actions such as education on reproductive health and providing knowledge for parents about the impact of early marriage on adolescents.